Lawson’s Psychological Critical Thinking Exam as an instrument to improve critical thinking - Marta-Natalia Torres-Domínguez; Itxaso Barberia; Javier Rodríguez-Ferreiro (Revista d'Innovació i Recerca en Educació)
INTRODUCTION. Critical thinking is vital in both science and daily life, being crucial for identifying anecdotal evidence, unfalsifiable hypotheses, biased data sampling, and unreliable causal connections. This study aimed to adapt Lawson’s revised version of the Psychological Critical Thinking Exam (PCTE) into Spanish, and to use it to assess improvement in Psychology students taking a module on reasoning.